Creating a Culture to Avoid Knowledge Hiding Within an Organization: The Role of Management Support - Jasimuddin, Sajjad M.; Saci, Fateh (Frontiers in Psychology, 2022)
Knowledge hiding is known to have negative consequences on organizational performance. The existing literature mainly focuses on the identification of antecedents and consequences of knowledge hiding. The studies pertaining to the top management role in creating a culture that stops concealing knowledge within an organization are limited. To fill that gap, the paper empirically address the knowledge sharing culture and to explore the management support to avoid knowledge hiding culture in an organization. This study based on an empirical study carried out in a United Kingdom-based laboratory within a high-tech global corporation, in which the atmosphere appeared conducive to knowledge sharing, and knowledge transfer appeared voluntary and spontaneous. The paper seeks to address why members of the case organization is reluctant about knowledge hiding among themselves. The study reveals that the management role is important in creating a culture that help discourage employees to withhold knowledge. The paper identifies the actions that top management takes to stop concealing knowledge within an organization. This study has provided several contributions. The findings of the study may be useful to managers and practitioners. For managers, this paper presents some important organizational factors that can be nurtured to avoid a knowledge-hiding culture in the organization. They can also take the management actions of the case organization as lessons to create a culture that encourage their employees to avoid knowledge hiding behavior.